In-Flight Emergency: A Simulation Case for Emergency Medicine Residents - Claire Hailey; Charles Lei; Laurie Lawrence (Association of American Medical Colleges, 2020)
Introduction In-flight medical emergencies are common occurrences that require medical professionals to manage patients in an unfamiliar setting with limited resources. Emergency medicine (EM) residents should be well prepared to care for patients in unusual environments such as on an aircraft. Methods We developed a simulation case for EM residents featuring a 55-year-old male passenger who suffers a cardiac arrest secondary to a tension pneumothorax. We conducted this case eight times during a 5-hour block of scheduled simulation time. Participants included EM residents of all training levels from one residency program. We arranged the simulation lab as an airplane cabin, with rows of chairs representing airplane seats and a mannequin in a window seat as the patient. Residents were expected to manage cardiac arrest and perform needle thoracostomy on the patient. Residents also evaluated and treated a flight attendant with a near syncopal episode. Throughout the case, residents were expected to practice teamwork skills, including leadership, communication, situational awareness, and resource utilization. Participants were debriefed and completed voluntary anonymous evaluations of the session. Results Seventeen EM residents participated in the simulation. Overall, all 17 found the simulation to be a valuable educational experience. In addition, all agreed or strongly agreed that they felt more prepared to respond to an in-flight emergency after participating in the simulation. Discussion This simulation was determined to be a valuable part of EM resident education. The challenges presented and skills practiced in this in-flight medical emergency simulation case are transferable to other resource-limited environments.